ANALYSIS OF THE INFLUENCE FROM HONG KONG EXTRADITION RULES DEMONSTRATION ON FOREX MARKET MOVEMENTS OF HONG KONGâS EXPORT AND IMPORT DESTINATION USING THE MINIMUM SPANNING TREE METHOD - Novianty
Econophysics is a discipline field that applies theories and methods by using Physics modeling to analyze complex data and usually used to solve problems in the economic field. The economic strength of a country is closely related to the exchange rate of its currency so it can be concluded that by analyzing the exchange rates of a country with other countries, it can indirectly analyze the economic relations of the two countries. The more amount of investment in a country’s currency can strengthen the value of that currency. Hong Kong as one of the centers of the world economy was hit by large-scale demonstrations that rejected the extradition constitution that the government wanted to implement. This demonstration could affect the economic performance of Hong Kong and the countries concerned, especially those do export and import directly. The effect of this event can be reviewed using the Minimum Spanning Tree method. This method can map the proximity of economic relations from several countries by making a graph based on the correlation of all foreign currencies. This method itself based on graph theory to describe the relationships between currencies of countries globally. Correlation coefficients will be calculated and converted into the distance values between two currencies exchange rates with different weights. Besides, the centrality of the foreign exchange market network will also be reviewed and analyzed.